The Mediating Effect of Social Anxiety on the Relationship Between Social Media Use and Body Dissatisfaction Among University Students - Jarrar, Yosra; Awobamise, Ayodeji O.; Nweke, Gabriel E. (Frontiers in Communication, 2022)
Body dissatisfaction has become increasingly common among women and young adults and has only become worse in the digital age, where people have increased access to social media and are in constant competition and comparisons with their “friends” on their different social media platforms. While several studies have looked at the relationship between social media and body dissatisfaction, there is an obvious dearth of empirical studies on the mediating role of social anxiety- a gap this study hoped to address. Using a cross-sectional research design, this study examined the mediating role of social anxiety on the relationship between social media usage and body dissatisfaction. The sample consisted of 432 students from Kampala International University and Victoria University in Uganda. The findings show a significant positive relationship between social media usage and body dissatisfaction. The findings prove that heavy users of social media are significantly more likely to suffer from body dissatisfaction. In a similar vein, the findings show that there is a significant positive relationship between social media usage and social anxiety. This suggests that people that frequently make use of social media have a much higher chance of suffering from social anxiety, that is the inability or difficulty to engage in social interactions, than people that rarely or moderately make use of social media. Finally, findings show that social anxiety mediates the relationship between social media usage and body dissatisfaction. It indicates that people with high levels of social anxiety are more likely to suffer from body dissatisfaction as a direct result of heavy social media usage. These findings imply that although heavy users of social media tend to have a more negative perception of their body, if these same users can properly engage in social interactions, then this might mitigate the negative effects of social media usage (in terms of body dissatisfaction).